Transparansi Beneficial Ownership Sebagai Upaya Control by Host State Indonesia Terhadap Perusahaan Multinasional - Firdaus, Achmad Dzulfadli (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Beneficial ownership is a type of ownership that can refer to an individual who is not legally written as the owner of the company, but has control and receives benefits from the company.Purposes of the Research: The purpose of this study is to find out the function of transparency of beneficial ownership as control by host state in order to find out who is actually beneficial ownership of multinational companies as an effort to prevent and eradicate violations committed by multinational companies.Methods of the Research: This study uses normative law research with an analytical approach to regulations derived from national and international law (statue approach).Results of the Research: First, there is a need to improve the mechanism for regulating the transparency of beneficial ownership in Indonesia to reveal the ultimate beneficial ownership. Second, if the transparency of beneficial ownership is truly enforced, then Indonesia can use the data as control by Indonesia's host state in overcoming risks and violations committed by multinational companies such as restrictions on share ownership, prevention of money laundering crimes, prevention of terrorism financing, business competition, consumer protection, environmental crimes and other violations in accordance with regulations in Indonesia.